La gran inscripción rupestre celtibérica de Peñalba de Villastar (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper provides a new analysis of a long Celtiberian inscription carved in the rock at Peñalba de Villastar (Teruel).  By  contrast to  most of the preceding interpretations, several phrases are now understood as containing placenames and spatial relationships. A tentative translation might be:“In Orosis and as far as the Tigino reaches, to Lugu we consecrate the fields. In Orosis and in Equeiso, the hills as well as the ploughed fields and the houses are consecrated to Lugu, that is, the houses of the bounded area”.